Understanding organizational wrongdoing II. - Fielder, J. (IEEE Engineering in medicine and biology magazine)
For part I see ibid., vol.22, p.156-7 (2003). Understanding ethical wrongdoing is a topic in moral psychology, the study of the psychological dimensions of ethics. This includes, but is not limited to cognitive, volitional, and behavioral aspects of ethical or unethical thinking and acting. A central question in moral psychology concerns the psychological factors that contribute to unethical decisions. Theories that illuminate unethical behavior in organizations are examined in this essay.